2017
DOI: 10.1016/j.molp.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The G-Protein β Subunit AGB1 Promotes Hypocotyl Elongation through Inhibiting Transcription Activation Function of BBX21 in Arabidopsis

Abstract: Hypocotyl development in Arabidopsis thaliana is regulated by light and endogenous hormonal cues, making it an ideal model to study the interplay between light and endogenous growth regulators. BBX21, a B-box (BBX)-like zinc-finger transcription factor, integrates light and abscisic acid signals to regulate hypocotyl elongation in Arabidopsis. Heterotrimeric G-proteins are pivotal regulators of plant development. The short hypocotyl phenotype of the G-protein β-subunit (AGB1) mutant (agb1-2) has been previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 105 publications
(211 reference statements)
0
30
1
Order By: Relevance
“…We then generated the agb1 hy5 hyh triple mutant and found that its hypocotyls were significantly longer than those of the agb1 hy5 double mutant, but were almost as long as those of the hy5 hyh double mutant ( Figure 3A-3H). Given that AGB1 functions through other factors such as BBX21 and BES1 (Xu et al, 2017;Zhang et al, 2018), these results suggest that AGB1 acts partially through HY5/HYH to repress photomorphogenesis.…”
Section: Agb1 Acts Partially Through Hy5 and Hyh To Repress Photomorpmentioning
confidence: 84%
See 2 more Smart Citations
“…We then generated the agb1 hy5 hyh triple mutant and found that its hypocotyls were significantly longer than those of the agb1 hy5 double mutant, but were almost as long as those of the hy5 hyh double mutant ( Figure 3A-3H). Given that AGB1 functions through other factors such as BBX21 and BES1 (Xu et al, 2017;Zhang et al, 2018), these results suggest that AGB1 acts partially through HY5/HYH to repress photomorphogenesis.…”
Section: Agb1 Acts Partially Through Hy5 and Hyh To Repress Photomorpmentioning
confidence: 84%
“…Likewise, the Arabidopsis and rice G-protein b subunits, AGB1 and RGB1, have been shown to localize to the plasma membrane, cytosol, and nucleus (Anderson and Botella, 2007;Yadav et al, 2014). It has been demonstrated recently that AGB1 promotes hypocotyl elongation by interacting with BBX21, a B-box-like zinc-finger transcriptional factor, and inhibiting its transcriptional activation activity rather than its DNA-binding activity (Xu et al, 2017). AGB1 also promotes hypocotyl elongation by interacting with BES1, a master transcription factor mediating BR signaling, and promoting its transcriptional activity (Zhang et al, 2018).…”
Section: Agb1 Physically Interacts With Hy5 To Inhibit Its Dna-bindinmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis , loss‐of‐function mutations in Gβ ( AGB1 ) lead to shorter hypocotyl, shorter petiole, and round lamina phenotypes caused by reduced cell division (Perfus‐Barbeoch et al 2004). Recent reports showed that AGB1 promotes hypocotyl elongation partially through directly inhibiting a B‐box (BBX)‐like zinc‐finger transcription factor (BBX21) (Xu et al 2017), and the shorter hypocotyl phenotype of agb1 can be partially suppressed by mutations in photoreceptors, cryptochrome 1 ( cry1 ) and phytochrome B ( phyB ) (Lian et al 2018; Xu et al 2018). Interestingly, AGB1 directly interacts with CRY1 or PHYB in a light‐dependent manner (Lian et al 2018; Xu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…BBX21 and BBX24 have a putative nuclear localization signal (NLS) sequence at their C-terminus, which 179 has been shown to be required for nuclear localization (Yan et al, 2011;Xu et al, 2017). In order to verify …”
mentioning
confidence: 99%